1984
DOI: 10.1159/000233463
|View full text |Cite
|
Sign up to set email alerts
|

Heterophile Antibodies in Sera of Patients with Chediak-Higashi Syndrome

Abstract: Sera of 6 patients with Chediak-Higashi syndrome and sera of their mothers were studied for heterophile antibodies. Sera of 5 patients as well as 5 sera of their mothers contained antibodies against trypsinized bovine erythrocytes, tissue sediments of guinea pig kidney or high molecular weight glycoprotein (HMWGP) of bovine erythrocyte stromata. The antibodies combining with HMWGP in enzyme immunoassay belonged to IgM and IgG classes. Although none of the sera had significant titer of agglutinins against sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Dicha mutación en LYST es la responsable de la disfunción fagocitaria e infecciones piógenas a repetición, lo cual se evidencia en antecedentes de abscesos cutáneos a repetición y debut con neumonía en el paciente presentado. En la línea roja, se describen anticuerpos heterófilos (IgG e IgM) contra componentes eritrocitarios, (11) y matriz lipídica anormal en la membrana de los eritrocitos originando disfunción en las proteínas de membrana, (12) con alteraciones en el transporte de calcio dependiente de ATP, al igual que en la membrana lisosomal de neutrófilos; (13) presentan alteraciones en la agregación y función plaquetaria. (14) Desde el momento de su ingreso este paciente presentó alteración de las tres líneas celulares, siendo congruente con la revisión de literatura.…”
Section: Discussionunclassified
“…Dicha mutación en LYST es la responsable de la disfunción fagocitaria e infecciones piógenas a repetición, lo cual se evidencia en antecedentes de abscesos cutáneos a repetición y debut con neumonía en el paciente presentado. En la línea roja, se describen anticuerpos heterófilos (IgG e IgM) contra componentes eritrocitarios, (11) y matriz lipídica anormal en la membrana de los eritrocitos originando disfunción en las proteínas de membrana, (12) con alteraciones en el transporte de calcio dependiente de ATP, al igual que en la membrana lisosomal de neutrófilos; (13) presentan alteraciones en la agregación y función plaquetaria. (14) Desde el momento de su ingreso este paciente presentó alteración de las tres líneas celulares, siendo congruente con la revisión de literatura.…”
Section: Discussionunclassified
“…SRBCs in routine laboratory practice are used to detect heterophile antibodies. ese antibodies are characteristically found in the sera of patients su ering from infectious mononucleosis, along with other clinical conditions, where the serum levels of heterophile antibodies have also been related to disease activity (Duverlie et al, 1989;Yoshida et al, 1980;Satoh et al, 1980;Moore and Dorner, 1980;Tamura et al, 1984). Since heterophile antibodies can be detected in an otherwise healthy population (Kakoma et al, 1987) their presence in the serum samples, sent to the laboratory for routine investigations and their ability to interfere with the results, cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies [7,11,12] by EIA with HMWGP of BRBC have demonstrated H-D antibod ies predominantly of IgM class in various diseases such as infectious mononucleosis, seropositive syphi lis, Chediak-Higashi disease and Kawasaki disease. In the present study, H-D antibodies of the IgG class were found in liver disease sera; 6% in acute hepatitis, 28% in chronic hepatits and 22% in liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%